The Effects of M&As on Firm Performance in a Developing and a Developed Country:Case of India and UK post the Global Financial Crisis - Surana, Shreya (2015)
Mergers, according to general expectation, are supposed to enhance the performances of the merging firms from what they would have been, had they not merged. A general hypothesis assumes that successful mergers increase the profitability of the firm (accounting and/or shareholder), which would be due to improved efficiency (operational or financial), reduced costs, enhanced market power, etc. The value of the merged firm is expected to be more than the individual firms put together before the merger. This is due to the generation of synergies. Though theoretically it all adds up, empirical evidence shows varied effects of M&As on firm performance. This research analyses 37 mergers that were completed in 2012 in the UK and India. The aim is to understand the effect of mergers on the companies’ accounting performance. The merged firms (acquirer and target before the merger) are studied over a period of five years using pre- and post- merger ratio analysis. A post- merger study is conducted on the sample of merged firms and a matched sample of non-acquiring firms put together in a panel dataset. The hypotheses constructed in this research are tested using paired t-tests and random effect regression models in STATA. The findings suggest that the merger activity has no significant impact on firm’s accounting performance. The main reason of insignificant influence of mergers is because the dataset has a large set of target firms that are considerably smaller in size than the acquiring firms. The findings and arguments are backed up by evidence from existing literature.